100 new scientific discoveries fascinating, unbelievable and mind-expanding stories - Kluger, Jeffrey (TIME Books, 2011)
A collection of stories about groundbreaking scientific discoveries covers such topics as animal behaviors, the characteristics of distant galaxies, and the incredible capacity of the human mind, in a volume that also provides a chronology of debunked scientific theories.